2021
DOI: 10.1021/acsnano.1c03252
|View full text |Cite
|
Sign up to set email alerts
|

Separable Microneedle Patch to Protect and Deliver DNA Nanovaccines Against COVID-19

Abstract: The successful control of coronavirus disease 2019 (COVID-19) pandemic is not only relying on the development of vaccines, but also depending on the storage, transportation, and administration of vaccines. Ideally, nucleic acid vaccine should be directly delivered to proper immune cells or tissue (such as lymph nodes). However, current developed vaccines are normally treated through intramuscular injection, where immune cells do not normally reside. Meanwhile, current nucleic acid vaccines must be stored in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 44 publications
0
82
0
1
Order By: Relevance
“…In addition, they can be equipped with features such as the ability to encapsulate fragile structures such as DNA, mRNA, protein subunits, and the ability to release these agents over time and then self-degrade thanks to site-specific-adjusted biodegradation. 77 , 163 165 …”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…In addition, they can be equipped with features such as the ability to encapsulate fragile structures such as DNA, mRNA, protein subunits, and the ability to release these agents over time and then self-degrade thanks to site-specific-adjusted biodegradation. 77 , 163 165 …”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…This makes them relevant for deployment in regions where cold storage facilities are scarce, a logistics hurdle for currently approved COVID-19 vaccines (Menon et al ., 2021 ). Initial reports of MNA-based vaccines assembled for delivery of DNA encoding the SARS-CoV-2 spike protein alongside adjuvant indicate that vaccine patches can be stored at room temperature for at least 30 days without sacrificing T cell responses (Yin et al ., 2021 ).…”
Section: Microneedle Arrays Provide An Accessible and Highly Modular Platform For Vaccination Against Current And Emerging Infectious Dismentioning
confidence: 99%
“…Ex vivo imaging of lymph node collected form sacrificed mice confirmed DNA vaccine migration to the lymph nodes. In vivo cellular immune responses showed that IFN-γ + CD4/8 + and IL-2 + CD4/8 + T cells or virus-specific IgG were significantly increased after vaccination ( 89 ).…”
Section: Efficacy Of Microneedle-based Vaccines In Preclinical and Cl...mentioning
confidence: 99%
“…From literature, MNs have been used to deliver different types of vaccines, including whole inactivated virus, subunit, DNA plasmid, recombinant protein, and antigen ( 89 , 95 , 109 ). However, ideal vaccine for MN delivery should be thermostable and maintain its antigenicity during manufacturing and sterilization processes ( 73 ).…”
Section: Vaccine Characteristics and Limitations Of Mns In Vaccine De...mentioning
confidence: 99%